Sketch of a Particularist Conception of the Laws of Logic (Culturas Científicas, 2021)
Logical Anti-Exceptionalism claims that Logic is like any other science. If this statement is correct, then Logic is not only revisable, but also everything that can be said about science applies to it, mutatis mutandis. The purpose of this article is to explore this consequence of Logical Anti-Exceptionalism, by approaching the Philosophy of Logic to Nancy Cartwright's theoretical framework of Nomological Machines. According to the latter, the truth of the scientific theories is not in the world, but in its models: highly controlled, stable, artificial, and specific systems, where systematizable and teachable regularities are manifested. I claim that the same can be said about Logic: it does not capture the Laws of Thought or Reason, because thought and reason are not necessarily governed by laws. Laws of Logic are about possible metaphysics: philosophical stories about what propositions, thoughts, truth and validity are. In order to illustrate and defend this thesis, I present an example of Nomological Machine for Classical Logic, based on Wittgenstein's Tractatus, and investigate some of its consequences. I conclude that this image of Logic has an impact on the problem of the revision of Classical Logic, as it shows that this revision does not necessarily respond to a rational process of adaptation of the theory to the facts. This is because the relevant “facts” are not prior to the theory itself but are shaped and driven by it.
Keywords: Logical Anti-Exceptionalism; Abductivism; Nomological Machines; Logical Revision; Philosophy of Logic